Alterations in brain leptin signalling in spite of unchanged CSF leptin levels in Alzheimer's disease. Issue 1 (2nd December 2014) - Maioli, Silvia; Lodeiro, Maria; Merino‐Serrais, Paula; Falahati, Farshad; Khan, Wasim; Puerta, Elena; Codita, Alina; Rimondini, Roberto; Ramirez, Maria J.; Simmons, Andrew; Gil‐Bea, Francisco; Westman, Eric; et al.
Summary Several studies support the relation between leptin and Alzheimer's disease (AD). We show that leptin levels in CSF are unchanged as subjects progress to AD. However, in AD hippocampus, leptin signalling was decreased and leptin localization was shifted, being more abundant in reactive astrocytes and less in neurons. Similar translocation of leptin was found in brains from Tg2576 and apoE4 mice. Moreover, an enhancement of leptin receptors was found in hippocampus of young Tg2576 mice and in primary astrocytes and neurons treated with Aβ1‐42. In contrast, old Tg2576 mice showed decreased leptin receptors levels. Similar findings to those seen in Tg2576 mice were found in apoE4, but not in apoE3 mice. These results suggest that leptin levels are intact, but leptin signalling is impaired in AD. Thus, Aβ accumulation and apoE4 genotype result in a transient enhancement of leptin signalling that might lead to a leptin resistance state over time.